Багатокритеріальна умовна оптимізація на основі генетичних алгоритмів - Sineglazov, Victor M.; Riazanovskiy, Kirill D.; Chumachenko, Olena I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2020)
This article takes on solving the problem of multicriteria conditional optimization. This problem is one of the most key tasks of the current time and has its application in many areas. Reuse of various existing algorithms for solving unconstrained optimization is proposed. Different methods of multicriteria unconditional optimization are reviewed. The advantages and disadvantages of each algorithm are analyzed. The algorithms modified to take into account the constraints. Additional algorithms of transition from solving an unconditional optimization problem to a conditional optimization problem are developed. A genetic algorithm SPEA2 was used to test the developed algorithms. Examples of solving the problem at hand using the aforementioned algorithms are presented. A comparative analysis of the final results was conducted.